2022
DOI: 10.29303/jppipa.v8i6.2182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Land Cover Change and Deforestation on Rainfall and Surface Temperature in New Capital City of Indonesia

Abstract: Land cover change and deforestation have a significant impact on climate change. This study investigates the effect of land cover change and deforestation on surface temperatures and extreme rainfall in the New Capital City of Indonesia (IKN), particularly in Samboja and Sepaku Subdistricts, East Kalimantan Province. Land cover change and deforestation were analyzed from Landsat 5 TM, 7 ETM+, and 8 OLI satellite data during 2001-2020. Land cover is divided into four classes: built-up land, water bodies, vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…In DJF and SON, the trend of CDD slightly decreases indicating more days with no rainfall in the seasons. Previous studies reported decreased trends of extreme rainfall over the IKN using 20-year of combined satellite and rainfall datasets 8,9 which contrast with our findings. The difference result occurs might be due to a longer dataset (43 years) of surface rainfall that we used in this study.…”
Section: Rainfall Distributioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In DJF and SON, the trend of CDD slightly decreases indicating more days with no rainfall in the seasons. Previous studies reported decreased trends of extreme rainfall over the IKN using 20-year of combined satellite and rainfall datasets 8,9 which contrast with our findings. The difference result occurs might be due to a longer dataset (43 years) of surface rainfall that we used in this study.…”
Section: Rainfall Distributioncontrasting
confidence: 99%
“…A previous study utilized satellite and three rain gauges data to analyze the trend of heavy rainfall characteristics over IKN between 2016-2020 and found that the trends slightly decrease 8 . Another study examined changes in land cover and deforestation affecting surface temperatures and extreme rainfall using several satellites during 2001-2020 and found that extreme number of very wet days (R95p), consecutive dry days (CDD), and max 1-day precipitation (RX1day) have decreased 9 . Former studies mostly used satellite data to analyze extreme rainfall over the IKN.…”
Section: Introductionmentioning
confidence: 99%
“…This can cause an increase in surface runoff and a decrease in groundwater recharge [49]. A significant decrease in vegetated land area is observed every year in the IKN area during last 20 years, followed by an increase in residential land and buildings (built-up area) and agricultural land [21]. This indicates deforestation and urbanization, which may cause a decrease in precipitation amount in the IKN.…”
Section: Resultsmentioning
confidence: 99%
“…Because rain in Kalimantan is influenced by atmospheric moisture content from the Pacific Ocean, the El Niño-Southern Oscillation (ENSO) also modulates extreme rain in Kalimantan [20]. In addition to climate change, deforestation and land-use change in Kalimantan have also contributed to the increase in extreme rainfall events [21]. The Madden-Julian Oscillation (MJO) can also significantly affect extreme rainfall events in Kalimantan.…”
Section: Introductionmentioning
confidence: 99%
“…This occurs due to an increase in the intensity of the greenhouse effect caused by the presence of gases in the atmosphere that absorb heat rays, especially infrared rays emitted by the earth. Global warming as a result of increasing concentrations of greenhouse gases, which trigger climate change, has become a global concern in recent decades (Safitri et al, 2022). This phenomenon has gained considerable attention due to the potential negative impacts of climate change on various economic sectors, which can threaten human life.…”
Section: Introductionmentioning
confidence: 99%